A reflective interview with Marcia Gentry and Scott Peters: The Hope Scale. (January 2015) - Greathouse, Dan; Shaughnessy, Michael F; Gentry, Marcia; Peters, Scott
The Hope Scale is an 11-item teacher-rating instrument designed to help identify academic and social components of giftedness. It provides insights from teachers who work with students on a daily basis, which may differ from the type of information yielded through achievement and ability tests. The Hope Scale development was made possible by the generous support of the Jack Kent Cooke Foundation, and it is available as a free download from the GERI website (www.purdue.edu/geri).